Monuments of History – a form of protection, a form of promotion, a form of management? - Szmygin, Boguslaw (Protection of Cultural Heritage, 2019)
The Monuments of History is a collection of over 100 most valuable monuments in Poland. At the same time, the Monuments of History are one of the 5 forms of protection of monuments, specified in Polish legislation. These circumstances make it necessary to assess the functioning of this form of the monuments protection. Many elements in the concept of the Monuments of History, the procedure of their nomination and the substantive assessment are taken over from the UNESCO World Heritage System. Therefore, this system may be a point of reference for the evaluation of the functioning of the Monuments of History. At the same time, on the basis of this comparison, it is possible to indicate directions for improving the functioning of the Monuments of History. The paper discusses fundamental aspects of the functioning of the Monuments of History – including the place and role of the Monuments of History in the Polish system of the monuments protection, the procedure of nomination, the procedure of evaluation, the relationship of the Monuments of History with the assets of the UNESCO World Heritage.